POLITIK HUKUM NASIONAL DAN HEGEMONI GLOBALISASI EKONOMI - Bariroh, Laili (Jurnal Review Politik, 2012)
This article will look at the relationship between  law and the situation surrounding the global economy. With descriptive analysis, explored how the legal and economic information as two subsystems, interacting. The interaction between the two subsystems are evident with the approach of the study of law and society. The development of global economy  have implications for the policies of national law automatically. Analysis shows that this is due to the preconditions which has done by economic and trading organizations. This tallows the political hegemony of the powerful state (forward) against weak countries (poor / developing).